The power of colour in geoheritage studies and marketing: some tentative reflections - Ruban, Dmitry A.; Mikhailenko, Anna V.; Yashalova, Natalia N. (Geologos, 2021)
Colour is a common physical property in exposures of unique geological objects, but is only marginally addressed in geoheritage literature. We here present our point of view on how this feature can be treated in geoheritage studies, with the general aim at setting up a broad discussion. Three functions of colour in geoheritage are outlined, namely geological interpretation (e.g., compositional and genetic peculiarities of sedimentary rocks), higher visibility due to colour contrast and aesthetic attractiveness to geotourists. Assessment of colour at geosites is challenging, especially because of uncertain colour nomenclatures. We propose to focus on colour identification, calculation of the number of colours, qualitative evaluation of colour contrast and comparison of colours of a given geological object to its landscape context. Geoheritage colours may have different meanings to geosite visitors, and colour-emotion associations revealed by national and international studies are important to trace these meanings.